Incremental relaying networks with energy harvesting relay selection: Performance analysis. Issue 12 (31st July 2018) - Bao, Vo Nguyen Quoc; Van, Nguyen Toan
Abstract: In this paper, we propose an incremental relaying network with energy harvesting–based relay selection, where the selected relay harvesting the largest energy from the source radio‐frequency signals among available ones will be the forwarder in the next hop using time switching mechanism. Employing incremental relaying, the destination will request the assistance from the selected relay when the direct link from the source to the destination is not good enough for decoding. Three cases at the destination are considered including no combining, selection combining, and maximal ratio combining. Our main contribution is to evaluate completely the performance of the proposed scheme over Rayleigh fading channels. The exact expressions of the system outage probability are derived and then verified by Monte‐Carlo simulations. We further conduct the asymptotic analysis to evaluate the diversity gain of the proposed scheme. We also propose a linear search algorithm to attain the optimal time switching ratio. The numerical results confirm the advantage of the proposed scheme over the direct transmission for a given average transmit power. In addition, it is shown that the system performance in terms outage probability, spectral efficiency, and system throughput can be improved by appropriately designing the switching (requesting) rate and the position of relays has significant effect on the system performance if the switching rate is greater than the target data rate. Abstract : This paper proposes an incremental relaying network with energy harvesting‐based relay selection, where the selected relay harvesting the largest energy from the source radio‐frequency signals among available ones will be the forwarder in the next hop using time switching mechanism. In this paper, we, for the first time, derive the exact OP for IR networks exploiting EH (IREH) relay selection with destination diversity combining of SC/MRC